PERAN PENGGUNA MEDIA SOSIAL WHATSAPP TERHADAP KOMUNIKASI ANTAR INTERPERSONAL KARYAWAN DI PERUSAHAAN GARMEN SAMKYUNG JAYA BUSANA - Ramdhani, Dini; Febri Anjani, Yka; Evi Yuliana, Margaretha (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2023)
This research aims to study the role of WhatsApp social network users in improving or breaking interpersonal communication between employees of the Samkyung Jaya Busana Garment Company. WhatsApp has become an inseparable part of everyday life, including in the work environment. The research results show that the use of WhatsApp can facilitate interpersonal communication between employees of the Garment Company Samkyung Jaya Busana. However, this research also identifies possible communication disruptions due to the use of WhatsApp. Too many notifications, ineffective group discussions, and constant changes in work schedules can disrupt employee productivity. Additionally, misunderstood or rude messages can create interpersonal tension. In summary, WhatsApp plays an important role in communication between employees of the Samkyung Jaya Busana textile company. Proper use and awareness of potential disruptions are essential to ensure WhatsApp contributes positively to communication in the work environment. By understanding the positive and negative impacts of social media use, businesses can develop appropriate guidelines to ensure effective and healthy communication between employees.